Interdisciplinarity in world history continuity and change - Abushouk, Ahmed Ibrahim; Zweiri, Mahjoob (Cambridge Scholars Publishing, 2016)
This book represents selected papers of an international conference convened by the Department of Humanities at Qatar University, Doha, in March 2013. Its theme was "Interdisciplinarity in History: An Old Method in New World Context".